Pyroptosis-related lncRNAs: A novel prognosis signature of colorectal cancer - Cai, Xing; Liang, Xiaoqing; Wang, Kun; Liu, Yin; Hao, Mengdi; Li, Huimin; Dai, Xiaofang; Ding, Lei (Frontiers in Oncology, 2022)
Pyroptosis is a newly discovered cell death method and participate in tumorigenesis. Long-non-coding RNAs (lncRNAs), implicated in many cancer cell progression including colorectal cancer (CRC). However, the potential role of pyroptosis-related lncRNAs (PRLs) on CRC is still unelucidated. Therefore, we retrieved transcriptome data of CRC patient from The Cancer Genome Atlas, using the univariate, multivariate Cox proportional hazard regression and Random Forest algorithm, constructed a newly risk model based on 8 PRLs: Z99289.2, FENDRR, CCDC144NL-ASL, TEX41, MNX1-AS1, NKILA, LINC02798 and LINC02381. Then we used Kaplan-Meier analysis to compare the survival of CRC patients and validated our risk model in external dataset (From the Gene Expression Omnibus databases, GEO17536, n=177 and GSE161158, n=250 respectively). To improve the clinical utility, a nomogram combining PRLs which could forecast the prognostic of CRC patients was established. In addition, we portray an immune landscape of CRC patients mediated by PRLs. Based on PRLs stratified two molecular subtypes, immune modulators, immune infiltration of tumor immune microenvironment, inflammatory pathway, TIDE and MSI score were analyzed in this study. Furthermore, we used three independent methods to predict PRLs-related chemotherapeutic drug sensitivity. Our comprehensive analysis of PRLs in CRC patients demonstrates the potential role of PRLs in the predict of treatment and prognosis of CRC patients, may contribute to understanding the molecular mechanisms of CRC and lead to formation newly effective immunotherapy strategies.